Respuesta :

Step-by-step explanation:

Given.

[tex]3x+5y=3[/tex]

[tex]x+2y=0[/tex]

Take the second equation and subtract 2y to both sides.

[tex](x+2y)-2y=0-2y[/tex]

[tex]x=-2y[/tex]

Substitute x into the first equation and simplify.

[tex]3x+5y=3[/tex]

[tex]3(-2y)+5y=3[/tex]

[tex]-6y+5y=3[/tex]

[tex]-y=3[/tex]

Invert.

[tex]y=-3[/tex]

Substitute Y into your second equation.

[tex]x+2y=0[/tex]

[tex]x+2(-3)=0[/tex]

[tex]x-6=0[/tex]

Add -6 to both sides.

[tex](x-6)+6=0+6[/tex]

[tex]x=6[/tex]

Answer:

(6, -3)

Answer:

(6,-3)

Step-by-step explanation:

Got it right on the test

Hope this helps :)